Identification of Microplastic Type and Abundance in East Coast of Karimun Besar Island, Riau Islands - Alpiansyah, Beni; Amin, Bintal; Galib, Musrifin (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
High anthropogenic activities on the east coast of Karimun Besar Island contribute a certain amount of wastes, especially plastics. Plastics will be degraded due to the natural mechanism of smaller parts and known as microplastics. Small size and widespread distribution has caused microplastics can be found widely in the ocean and coastal areas. This study was conducted in March 2020, located on the east coast of Karimun Besar Island, Province of Riau Islands. The purpose of this study was to know the presence of microplastics in its coastal water. The method used in this study was a survey method by taking samples from four stations with suspected different anthropogenic activities. The results showed that the lowest abundance of microplastics in the coastal waters of the east coast of Karimun Besar Island was 63,33 particles/m3 and the highest was 161,66 particles/m3, with the dominant type found was fibre. The abundance of the microplastic between station was found to be significantly different (p < 0,05).